O trinômio gênero/raça/classe no romance feminista contemporâneo O trinômio gênero/raça/classe no romance feminista contemporâneo - Susana Bornéo Funck (Ilha do Desterro, 2008)
In the eighties, issues related to racial and ethnic differences and their correlation with social classes became central in the theorization and political practice of feminism. This essay examines contemporary women writers from English
speaking countries—Margaret Laurence, Marge Pierce and Angela Carter—, showing how issues of gender/race/class are problematized in their works Na década de 80, as questões relativas às diferenças raciais e étnicas e sua correlação com classes socias tornaram-se centrais nas teorizações e prática política do feminismo. Este trabalho examina escritoras contemporâneas de língua inglesa—Margaret Laurence, Marge Pierce e Angela Carter –, mostrando como o trinômio gênero/raça/classe é problematizado em suas obras.